Ocular effect of preservative free and bak containing Travoprost - a tertiary care hospital based study - GYANENDRA KUMAR; RAKESH CHANDRA CHAURASIA; S.P. SINGH (International Journal of Pharma and Bio Sciences, 2017)
Elevated intraocular pressure (IOP) is a leading risk factor for the development of primary open angle glaucoma, and reducing IOP is shown to be imperative to slow disease progression in this disease. Prostaglandin analogs showed advantages over other medical treatments and are presently the initial medication of choice. PGAs (latanoprost and travoprost) are typically administered in multi-dose bottles that contain preservatives to ensure sterility. Benzalkonium chloride (BAK, quaternary ammonium compound) is the most commonly used preservative in ophthalmic medications. Frequent dosing with benzalkonium chloride (BAK) containing ophthalmic solutions may lead to occular adverse effects. This study was done to evaluate and compare the effect of benzalkonium chloride (BAK) containing and preservative free ophthalmic solution of travoprost on ocular surface in patients with primary open angle glaucoma at regional institute of ophthalmology MotiLal Nehru Medical College Allahabad Uttar Pradesh. 47 newly diagnosed POAG patients were included in this prospective study. Patients were randomly divided in two groups. Patients in Group1 were treated with BAK preserved travoprost 0.004% and patients in Group 2 were treated with BAK free travoprost 0.004%. Intraocular pressure (IOP), hyperemia score and tear break up time (TBUT) were assessed at baseline, week 4 and 3 month after starting treatment.IOP decreased in all patients from baseline to 3month final visit (26.07± 2.48 mmHg versus 17.50 ± 1.79mmHgÍ¾ P < 0.0001 for Group 1 and 25.20 ± 2.01 mmHg versus 16.92 ± 2.18 mmHgÍ¾ P<0.0001 for Group 2).Hyperemia score for group1was increased (0.36±0.48 vs 0.76±0.67; p<0.003) at week 2 and statistically remained same for group 2 (0.38±0.36 vs 0.41±0.47; p= 0.640) at week 2. Mean TBUT decreased from 12.26±2.28seconds at baseline to 8.29±1.17seconds at 3month final visit (p<0.0001) for Group1. Mean TBUT decreased from 12.12±2.57 seconds at baseline to 11.75±2.33seconds at 3month final visit (p=0.053) for Group2. This study showed that BAK preserved travoprost 0.004% and BAK free are effective medication in newly diagnosed POAG patients. Long term use of BAK containing travoprost may negatively influence ocular surface health.